Leaf temperature of soybean grown under elevated CO2 increases Aphis glycines (Hemiptera: Aphididae) population growth - O'Neill, Bridget F. (2011)
Abstract Plants grown under elevated carbon dioxide (CO2) experience physiological changes that influence their suitability as food for insects. To determine the effects of living on soybean (Glycine max Linnaeus) grown under elevated CO2, population growth of the soybean aphid (Aphis glycines Matsumura) was determined at the SoyFACE research site at the University of Illinois, Urbana-Champaign, Illinois, USA, grown under elevated (550 μL/L) and ambient (370 μL/L) levels of CO2. Growth of aphid populations under elevated CO2 was significantly greater after 1 week, with populations attaining twice the size of those on plants grown under ambient levels of CO2. Soybean leaves grown under elevated levels of CO2 were previously demonstrated at SoyFACE to have increased leaf temperature caused by reduced stomatal conductance. To separate the increased leaf temperature from other effects of elevated CO2, air temperature was lowered while the CO2 level was increased, which lowered overall leaf temperatures to those measured for leaves grown under ambient levels of CO2. Aphid population growth on plants grown under elevated CO2 and reduced air temperature was not significantly greater than on plants grown under ambient levels of CO2. By increasing Glycine max leaf temperature, elevated CO2 may increase populations of Aphis glycines and their impact on crop productivity. © 2011 The Authors Journal compilation © Institute of Zoology, Chinese Academy of Sciences.